2014
DOI: 10.1099/mic.0.081505-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline tolerance mediated by gene amplification in Bacillus subtilis

Abstract: Bacillus subtilis can acquire a higher tolerance to tetracycline by increasing the gene dosage of its resistance gene tetB. In this study, we estimated the multiplication effect of tetB on tetracycline tolerance. Cells harbouring multiple copies of tetB were found to comprise approximately 30 % of the total tetracycline-resistant cell population when selected on medium containing 10 mg tetracycline ml "1. Disruption of recA resulted in a significant decrease in the frequency of tetB amplification. Although fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…107 Under strong selection, multiple copies of a gene mediating survival may emerge within a strikingly small number of generations and disappear immediately after selection is removed. 108,109 Given high replication fidelity, the above-discussed mechanisms may be crucial in shortening the time gap between new challenges and the arrival of mutations that promote survival. 110 It is not trivial to establish direct causality between stress, the induction of genetic changes, and adaptation.…”
Section: Mutagenic Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Under strong selection, multiple copies of a gene mediating survival may emerge within a strikingly small number of generations and disappear immediately after selection is removed. 108,109 Given high replication fidelity, the above-discussed mechanisms may be crucial in shortening the time gap between new challenges and the arrival of mutations that promote survival. 110 It is not trivial to establish direct causality between stress, the induction of genetic changes, and adaptation.…”
Section: Mutagenic Hotspotsmentioning
confidence: 99%
“…Duplications can vary from gene segments to whole genomes and may also be considered as “adaptive mutations,” whenever they are stress‐induced and auto‐amplified 107 . Under strong selection, multiple copies of a gene mediating survival may emerge within a strikingly small number of generations and disappear immediately after selection is removed 108,109 …”
Section: Mutagenic Hotspotsmentioning
confidence: 99%
“…In the present study, both pathways, SHDIR and SHIIR, may be involved in B. subtilis rrn amplification. It was recently reported that recA-independent duplication of the tetB gene, which confers tetracycline resistance in B. subtilis (Wannarat et al 2014), may not require RecA activity for the initial duplication event.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of B. subtilis is significantly inhibited by all tested transporters, with MICs of 2-4 even lower than that of antibiotic tetracycline (MIC = 11.3 µM). 29 Noteworthy, the MIC values for 1-4 correlate with their H + Cl − transport activity in liposomal assays. Remarkably, thioamide 2 exhibits particularly strong antibacterial properties against S. aureus, the second leading pathogen responsible for antimicrobial resistance-associated deaths in 2019.…”
Section: Biological Studiesmentioning
confidence: 99%
“…In fact, the antibacterial properties of synthetic anionophores often correlate with their anion transport activity. 8,9,23,24,25,26,29 However, some deviations from this rule 27 indicate, that the rate of anion transport is not the only factor responsible for antimicrobial activity of synthetic ionophores. Further biological studies with transporters that act via different mechanisms may be helpful in order to learn more about the origins of the antibacterial properties of ionophores.…”
Section: Biological Studiesmentioning
confidence: 99%